1H-[13C] NMR measurements of [4-13C]glutamate turnover in human brain. - Rothman, D L (1992)
A limitation of previous methods for studying human brain glucose metabolism, such as positron emission tomography, is that metabolic steps beyond glucose uptake cannot be studied. Nuclear magnetic resonance (NMR) has the advantage of allowing the nondestructive measurement of 13C distribution in specific carbon positions of metabolites. In this study 1H-[13C] NMR spectroscopy in conjunction with volume localization was used to measure the rate of incorporation of 13C isotope from infused enriched [1-13C]glucose to human brain [4-13C]glutamate. In three studies C4 glutamate turnover time constants of 25, 20, and 17 min were measured in a 21-cm3 volume centered in the region of the visual cortex. Based on an analysis of spectrometer sensitivity the spatial resolution of the method can be improved to < 4 cm3. In conjunction with metabolic modeling and other NMR measurements this method can provide a measure of regional rates of the brain tricarboxylic acid cycle and other metabolic pathways.